An action research study on AI video vs. written feedback: enhancing undergraduate academic writing and critical thinking - Sandra Baroudi; Nida Mubeen; Suha Karaki (Cogent Education)
This action research explores how AI-assisted feedback formats influence students’ academic writing and critical thinking, a gap particularly relevant in the digital learning landscape. This study involved 40 undergraduate Emirati students divided into two groups, receiving either AI-generated video or written feedback across three assignments. Using a quantitative design , data were gathered using standardized critical thinking and academic writing skills rubrics. Additionally, students completed post-surveys to capture their perceptions, engagement levels and use of AI tools in the learning process. Results showed written feedback significantly improvemed critical thinking (M = 2.80, SD = 0.75) compared to video feedback (M = 2.59, SD = 0.39, p < 0.05). However, video feedback enhanced students’ engagement with AI tools, fostering creativity and ethical AI use. While both formats enhanced academic writing, written feedback provided clearer structural guidance, whereas video feedback promoted problem-solving. The study suggests hybrid feedback models can better address diverse learning needs and support effective AI integration. However, the study’s small sample size and short duration limit generalizability, highlighting the need for further longitudinal research.